Awkward questions: language issues in the 2011 census in England. Issue 2 (7th February 2018) - Sebba, Mark
ABSTRACT: The 2011 Census in England broke new ground, as a question about language had never previously been asked. After stakeholder consultations and a series of trials, the census authority decided on two questions based on earlier censuses in the USA: one about the respondent's 'main language' and another about proficiency in English. This paper provides a critique of the census questions, showing how the pressure to produce questions which were straightforward to answer and consistent with the predominant monolingual ideology led to the choice of two questions which were problematic in different ways. This raises doubts about the validity of the questions themselves and the usefulness of the data collected.